Morphological structures and self-cleaning properties of Nano-tio2 coated cotton yarn at different washing cycles - Mirra Edreena Sallehudin; Nor Dalila Nor Affandi; Ahmad Mukifza Harun; Mohammad Khursheed Alam; Liliana Indrie (Molecular Diversity Preservation International (MDPI), 2023)
Titanium dioxide (TiO2 ) has an extraordinary photocatalytic activity and it effectively provides self-cleaning properties for cotton products. With the presence of succinic acid, it helps the adherence of the TiO2 nanoparticles on cotton surfaces. However, the ability of succinic acid to keep the TiO2 adhered on cotton after washing is not yet fully understood. Therefore, this study aimed to investigate the effects of washing cycles on nano-TiO2 coated cotton yarn with the aid of succinic acid on the morphological structures and self-cleaning properties. In this study, the nano-TiO2 was synthesized using a hydrothermal method. The cotton yarn was coated with succinic acid and was later dipped in a nano-TiO2 nanoparticles suspension. The nano-TiO2 coated yarn samples then underwent the 5th, 10th, 15th, and 20th wash cycles and were tested for morphological structures and self-cleaning. The self-cleaning properties of the nano-TiO2 coated yarn were determined using the depth of colour stain. The depth of the colour stain was presented as K/S value, where K and S are corresponded to the absorption and scattering coefficients of the stained fabric, respectively. From the analysis, our synthesized nano-TiO2 had a size of 20–50 nm range with a band gap of 3.06 eV. After coating, the nano-TiO2 coated cotton yarn changed in its morphological structure at 5th, 10th, 15th , and 20th wash cycles, respectively. At the 20th wash cycle, the weight (%) of the Ti element continued to decrease up to 4.45%, reducing the photocatalytic activity with the K/S value close to the stained yarn, which was about 0.4. The 5th wash cycle maintained a good photocatalytic activity with the K/S value of 0.06 near to the K/S value of the unstained cotton yarn. The presence of succinic acid in the nano-TiO2 coated cotton yarn provided good selfcleaning properties up to the 15th wash cycle. By undertaking this study, an enhanced cotton property has been developed that will benefit the textile and clothing industry. This nano-TiO2 coated cotton the has potential to be used for daily apparel and sportwear.